Fully Solution‐Processed Transparent Nonvolatile and Volatile Multifunctional Memory Devices from Conductive Polymer and Graphene Oxide. (29th June 2017) - Shi, Rui; Wang, Xiangjing; Wang, Zhan; Cao, Lijun; Song, Mengya; Huang, Xiao; Liu, Juqing; Huang, Wei
Abstract : A transparent multifunctional memory array with the configuration of m‐poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonic acid) (PEDOT:PSS)/graphene oxide (GO)/m‐PEDOT:PSS is fabricated through a full‐solution process. Dimethyl sulfoxide‐doped PEDOT:PSS thin films as the top and bottom electrodes are facilely prepared by spray coating, and a GO film as the active medium layer is obtained by spin coating. The thus‐fabricated device exhibits nonvolatile and volatile multifunctional memory effects, with an ON/OFF current ratio of 10 4 and 10 2 for the nonvolatile and volatile modes, respectively. Both the ON and OFF states are stable under the retention test in the nonvolatile memory mode, as well as during the endurance test in the volatile memory mode, demonstrating advantageous features of stable operation, permanent lifetime, excellent reproducibility, and reliable switching endurance. Moreover, the devices also show a 70% transmission of visible light. Their high transparency, combined with the multifunctional property and simple device configuration, makes these devices promising carbon‐based building blocks in a variety of electronic systems such as transparent electronics, electronic labels, radio frequency identification, internal memory, and databases. Most importantly, the simple full‐solution fabrication process is anticipated to potentially afford industrial‐scale low‐cost fabrication of future electronic devices. Abstract : A transparent multifunctional memory array, with graphene oxide as an active medium layer and m‐poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonic acid) as both the top and bottom electrodes, is fabricated through a full‐solution process. The device exhibits nonvolatile and volatile memory effects, together with merits of stable operation, permanent lifetime, low misreading probability, excellent reproducibility, and reliability.